Evil star - Horowitz, Anthony, 1955- (New York : Scholastic, 2007)
Having locked the Raven's gate, fourteen-year-old Matt travels to Peru where he meets the second of the five gatekeepers and works with him to try to stop the opening of a second gate somehow related to the Nazca Lines.
"Apple series.".
Prequel to: Nightrise.
Sequel to: Raven's gate.
Booklist.
School Library Journal.
Wilson's Junior High School.
Keywords: Incas -- Fiction; Indians of South America -- Peru -- Fiction; Supernatural -- Fiction; Incas -- Fiction; Indians of South America -- Peru -- Fiction; Supernatural -- Fiction; Incas -- Fiction; Native Americans -- South America -- Fiction; Supernatural -- Fiction; Nazca Lines Site (Peru) -- Fiction; Peru -- Fiction; Nazca Lines Site (Peru) -- Fiction; Peru -- Fiction; Nazca Lines Site (Peru) -- Fiction; Peru -- Fiction